2018
DOI: 10.1111/head.13404
|View full text |Cite
|
Sign up to set email alerts
|

Headache attributed to TMD Is Associated With the Presence of Comorbid Bodily Pain: A Case‐Control Study

Abstract: In a population of patients with chronic TMD seeking pain management, TMDH was significantly associated with an increased number of self-reported bodily pain conditions, a greater number of painful sites in the head and neck regions, and higher TMD pain intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In the univariate analyses of many measured characteristics of facial pain, HATMD was associated only with pain-free jaw opening and familiar examination-evoked pain of masticatory muscles and TMJ. While the association with evoked pain of masticatory muscles and TMJ is consistent with our previous report [ 15 ], the lack of association with facial pain intensity is not. The discrepancy could be due to differences in criteria used to select study participants.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the univariate analyses of many measured characteristics of facial pain, HATMD was associated only with pain-free jaw opening and familiar examination-evoked pain of masticatory muscles and TMJ. While the association with evoked pain of masticatory muscles and TMJ is consistent with our previous report [ 15 ], the lack of association with facial pain intensity is not. The discrepancy could be due to differences in criteria used to select study participants.…”
Section: Discussionsupporting
confidence: 91%
“…HATMD occurs frequently in TMD patients, with prevalence ranging from 5.4% to 29.3% in tertiary orofacial pain clinics [ 15 , 16 ]. However, little is known about the biopsychosocial characteristics that might be associated with HATMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Headaches are common among the general population. Recent studies had reported that there is a significant positive association between temporomandibular pain and primary headaches (tension type headache and migraine) [41][42][43][44] . Epidemiological studies assessed that headache are present in 50 to 80% of individuals with TMD, compared to 13 to 23% among those without TMD and with females being more frequently affected 41,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Considerable indirect evidence seems to indicate that not only increased pain facilitation but also ineffective pain inhibition represents a predisposition for chronic pain. This view is supported by the fact that many chronic pain syndromes (e.g., FM, TMJ disorder, irritable bowel syndrome, headache, and chronic fatigue syndrome) are associated with hypersensitivity to painful stimuli and reduced endogenous pain inhibition [30].…”
Section: Discussionmentioning
confidence: 99%